2021
DOI: 10.1002/ps.6291
|View full text |Cite|
|
Sign up to set email alerts
|

Inheritance mode and metabolic mechanism of the sulfoximine insecticide sulfoxaflor resistance in Oxycarenus hyalinipennis (Costa)

Abstract: BACKGROUND Dusky cotton bug (DCB), Oxycarenus hyalinipennis (Costa) (Hemiptera: Lygaeidae), is a key insect pest of cotton. It causes huge losses to cotton and many other economically important crops. Sulfoxaflor is a newly introduced systemic insecticide that is effective against many sap‐feeding insect pests such as aphids, whiteflies and true bugs. The present study was designed to characterize the inheritance of sulfoxaflor resistance in DCB. Moreover, the role of synergists in reducing sulfoxaflor resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Normally, the polygenic type of resistance grows slowly and dilutes quickly by the breeding of susceptible and resistant individuals in comparison with the monogenic type of resistance [ 31 , 72 ]. This dilution of resistant alleles by hybridization boosts the flow of susceptible alleles [ 58 , 73 ]. In this study, the backcrosses revealed polygenic nature of Dipel resistance in E. vittella .…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the polygenic type of resistance grows slowly and dilutes quickly by the breeding of susceptible and resistant individuals in comparison with the monogenic type of resistance [ 31 , 72 ]. This dilution of resistant alleles by hybridization boosts the flow of susceptible alleles [ 58 , 73 ]. In this study, the backcrosses revealed polygenic nature of Dipel resistance in E. vittella .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that the inheritance of resistance to sulfoxaflor was incompletely dominant and polygenic under laboratory conditions. 41 Furthermore, synergism bioassays indicated that synergists such as DEF (S,S,S-butyl phosphorotrithioate) had significantly increased the toxicity of sulfoxaflor while PBO (piperonylbutoxide) did not alter the susceptibility of O. hyalinipennis in the Sulfo-Sel Pop. 41 The current results of this study indicate that the O. hyalinipennis has the ability to develop resistance to many insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, synergism bioassays indicated that synergists such as DEF (S,S,S-butyl phosphorotrithioate) had significantly increased the toxicity of sulfoxaflor while PBO (piperonylbutoxide) did not alter the susceptibility of O. hyalinipennis in the Sulfo-Sel Pop. 41 The current results of this study indicate that the O. hyalinipennis has the ability to develop resistance to many insecticides. 7,22,60 Therefore, the Field-Pop of O. hyalinipennis was selected with sulfoxaflor under the continuous laboratory conditions for 18 generations and showed 3064.92-fold and 107.69-fold resistance in a selected strain compared to the UNSel-Pop and Field-Pop, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations